Perbandingan Kebijakan Kurs di Asia Tenggara Menggunakan Banxia Frontier Analysis (2013-2023) - Sabila, Ahya Bazlin (Journal of Economic and Business Analysis, 2025)
This research evaluates the efficiency of exchange rate policies in Southeast Asian countries from 2013 to 2023 using the Banxia Frontier Analysis method. By analyzing macroeconomic indicators such as inflation rates, GDP growth, and interest rates, the study identifies disparities in policy effectiveness among these countries. The findings reveal that Brunei Darussalam, Singapore, and Malaysia demonstrate high efficiency in exchange rate management, achieving significant stability with minimal input. This success is attributed to their responsive and well-structured monetary policies, which adapt effectively to global economic dynamics, fostering competitiveness and attracting foreign investment. In contrast, countries such as Myanmar and Thailand exhibit low efficiency, characterized by high input usage and suboptimal output. These inefficiencies are linked to inconsistent economic growth, high inflation, and rigid monetary policies. This study highlights the critical role of efficient exchange rate management in promoting economic stability and sustainable growth. Policymakers are encouraged to adopt more adaptable and resource-efficient strategies to improve stability and resilience against external economic pressures.